2022
DOI: 10.1039/d2dt02277j
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of mixed conductor Ba1−xGd1−yLax+yCo2O6−δ

Abstract: Ba1-xGd1-yLax+yCo2O6-δ (BGLC) compositions with large compositional ranges of Ba, Gd, and La have been characterised with respect to phase compositions, structure, and thermal and chemical expansion. The results show a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It has previously been shown that BGLC undergoes a phase transition from a Pmmm a2b2c to a Pmmm 2a3b3c supercell upon hydration. 38 The supercell contains some oxygen sites with a favourable environment for proton formation and may thus act as traps limiting proton mobility. Fig.…”
Section: Partial Protonic Conductivity Inmentioning
confidence: 99%
“…It has previously been shown that BGLC undergoes a phase transition from a Pmmm a2b2c to a Pmmm 2a3b3c supercell upon hydration. 38 The supercell contains some oxygen sites with a favourable environment for proton formation and may thus act as traps limiting proton mobility. Fig.…”
Section: Partial Protonic Conductivity Inmentioning
confidence: 99%